THE EFFECT OF SERVICE QUALITY ON GENERAL PATIENT SATISFACTION (Survey At The RSIA Husada Bunda Salo Sub-District Kampar District) - Doddy Audi Sandra; Arman Arman; Litra Diantara (STIE Bangkinang Publishing, 2021)
Research to determine the effect of service quality with dimensions tangible, empathy, reliability, responsiveness and assurance with simulthan and partial on general patient satisfaction at the RSIA Husada Bunda Salo Sub-District Kampar District. Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. Sampling is done accidental sampling method as many is 100 families of general patients are hospitalized at RSIA Husada Bunda Salo Sub-District Kampar District. Based on the simulthan test results, the variable of tangible, empathy, reliability, responsiveness and assurance have a significant effect on general patient satisfaction at the RSIA Husada Bunda Salo Sub-District Kampar District. While based on the partial test results, the variable of tangible, empathy, reliability, responsiveness and assurance have a significant of individual effect on general patient satisfaction at the RSIA Husada Bunda Salo Sub-District Kampar District. The closeness of the relationship that occurs between the atractiveness tangible, empathy, reliability, responsiveness and assurance on the patient satisfaction at the RSIA Husada Bunda Salo Sub-District Kampar is very strong with a correlation coefficient R of 86,0%. While contribution of independent variables to the dependent variables is equual to 72,9% .